Polarization-controlled quasi-phase-matching of high harmonic generation - Liu, L; O'Keeffe, K; Hooker, S (2013)
A new class of quasi-phase matching high harmonic generation is proposed where the polarization of the driving field is controlled in a waveguide. The first circularly polarized quasi-phase matched source is shown to be possible. © Owned by the authors, published by EDP Sciences, 2013.